2020
DOI: 10.1186/s13756-020-00754-1
|View full text |Cite
|
Sign up to set email alerts
|

Increase of vancomycin-resistant Enterococcus faecium strain type ST117 CT71 at Charité - Universitätsmedizin Berlin, 2008 to 2018

Abstract: Background: In addition to an overall rise in vancomycin-resistant Enterococcus faecium (VREfm), an increase in certain strain types marked by sequence type (ST) and cluster type (CT) has been reported in Germany over the past few years. Outbreak analyses at Charité-Universitätsmedizin Berlin revealed the frequent occurrence of VREfm ST117 CT71 isolates in 2017 and 2018. To investigate whether ST117 CT71 have emerged in recent years or whether these strains have been circulating for a longer time, we retrospec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
5
21
0
Order By: Relevance
“…Two of these genes, pilA and hyl , were carried on plasmids as described in the literature ( Freitas et al, 2018 ; Gao et al, 2018 ). Our data are in line with the observation that the pattern of virulence and resistance genes herewith detected is linked to “high risk” Enterococcus strains ( Weber et al, 2020 ) and is consistent with the classification within the major putative virulence markers typical of clade A1 as proposed by Freitas et al (2018) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Two of these genes, pilA and hyl , were carried on plasmids as described in the literature ( Freitas et al, 2018 ; Gao et al, 2018 ). Our data are in line with the observation that the pattern of virulence and resistance genes herewith detected is linked to “high risk” Enterococcus strains ( Weber et al, 2020 ) and is consistent with the classification within the major putative virulence markers typical of clade A1 as proposed by Freitas et al (2018) .…”
Section: Discussionsupporting
confidence: 91%
“…Here, we describe the genomic makeup of 39 VREfm strains isolated from 2011 until 2017, including two consecutive outbreak isolates sharing the same genetic background and compare them with VSEfm isolates. These isolates belonged to ST117, a lineage frequently associated with nosocomial outbreaks ( Papagiannitsis et al, 2017 ; Zhou et al, 2018 ; Abdelbary et al, 2019 ; Falgenhauer et al, 2019 ; Liese et al, 2019 ; Pinholt et al, 2019 ; Eisenberger et al, 2020 ; Weber et al, 2020 ) and classified as part of the hospital-associated clade A1 ( Lebreton et al, 2013 ). A previous study showed that strains belonging to this clade have a larger genome size suggesting that the acquisition of new traits occurred whilst persisting in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly higher VR E. faecium prevalence of 1.5 per 100 patients screened in 2015 compared to 0.8 in 2014 can be explained by the dynamics of VR E. faecium epidemiology in the last few years. As reported, at Charité University Hospital, the number of isolates representing the ST117 CT71 strain increased by 36.7% (p<0.001) [ 31 ]. German national nosocomial infection surveillance system (KISS) data confirms a trend of increasing VRE positivity in hospitalised patients between 2008 and 2016 that is in accordance with European surveillance data [ 3 ], [ 35 ].…”
Section: Discussionmentioning
confidence: 76%
“…One cause might be the regional emergence of specific VRE strains. In clinical and surveillance samples from different wards at Charité University Hospital from 2008 to 2018, a significant increase in VRE strain sequence type (ST)117 cluster type (CT)71 was reported [ 31 ]. Therefore, we can assume that the rising VRE prevalence at Charité University Hospital is due to strain ST177 CT71.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation